KONSEP SISTEM PENDIDIKAN ISLAM DALAM PERSPEKTIF HADIS: TINJAUAN SISTEMATIS LITERATUR - Sinaga, Mitha Shaskila Sinaga; Muhammad Nur Aziz Saputra; Marhumah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the concept of the Islamic education system from the perspective of hadith through a Systematic Literature Review (SLR) approach using the PRISMA protocol. The research is grounded in the significance of hadith as a primary source of Islamic teachings after the Qur'an, encompassing educational principles such as goals, roles of educators and learners, teaching methods, and instructional content. A total of 50 selected scholarly articles were thematically analyzed. The findings reveal that the Prophet’s hadiths offer both normative and practical foundations for Islamic education, emphasizing character formation, spirituality, and social transformation. The hadith-based Islamic education system is holistic, contextual, and transformative. Moreover, Islamic education has shown resilience over time due to its roots in divine revelation and the Prophet’s traditions. This study underscores the importance of integrating hadith values into the development of the Islamic education system to address contemporary global challenges.